New-Age-Diskurs in der polnischen Literaturwissenschaft, Literaturkritik und Lyrik der 70er und 80er Jahre - Miszewski, Brigitta (Peter Lang International Academic Publishing Group, 1995)
In the present work, an individualistic and mystical oriented flow of Polish literary criticism, literary criticism and poetry of the late 70s and 80s, characterized by the idea of ​​a
Keywords: 70er; 80er; Diskurs; eines; Jahre; Literaturkritik; Literaturwissen; Literaturwissenschaft; Lyrik; Maria Janions; marxistische Hermeneutik; Miszewski; Neue Privatheit; polnische Neoromantik; polnischen; Rekonstruktion; Strukturalismus-Kritik; Weltbildes; linguistics